El objetivo de valor constitucional de la posibilidad de disponer de una vivienda digna en el derecho francés - Kurlat Aimar, José Sebastián (2017)
The text of the French Constitution of 1958 and the texts to which it refers do not expressly mention a right to housing. However, this did not prevent the constitutional judge to consegrate an objective of constitutional value: the possibility for everyone to have access to adequate housing. This sui generis mechanism integrates the constitutional rules and principles -the socalled constitutional block-. This text questions the nature and scope of this constitutional objective. Firstly, we will analyze its consecration. Secondly, we will focus on its primary vocation: framing the legislation. Finally, we will study its main contentious consequences. Indeed, the judge finds this constitutional objective within the 10th and 11th paragraph of the Preamble of 1946 and in the Principle of the dignity of the person. At the same time, the objective of constitutional value operates in a teleological way, for the future, resulting in limited progressiveness and a possible penalty of the unconstitutional omission. Its implementation involves certain tensions with Property rights and other rights and freedoms.